أثر برنامج تدريبي مقترح بطريقة تدريب التكراري في تطوير السرعة و مهارة الجري بالكرة لدى لاعبي كرة القدم فئة أقل من 15 سنة - بوجلال لطفي (My University, 2023)
.................................................................abstract................................................................. Study title: The effect of a proposed training program using the repetitive training method in developing the speed and skill of running with the ball for soccer players under 15 years old. The aim of the study: To know the effect of repetitive training within a proposed training program to develop the speed and skill of running with the ball for soccer players under 15 years old. Study problem: The proposed training program using repetitive training contributes to the development of speed and the skill of running with the ball for soccer players under 15 years old. study hypotheses 1/ The general hypothesis: The proposed training program using repetitive training positively affects the development of speed and the skill of running with the ball for soccer players under 15 years old. 2/ Partial Hypotheses: -There are statistically significant differences between the pre and post measurements of the experimental group for the 30-meter speed test for football players under 15 years old. - There are statistically significant differences between the pre and post measurements of the experimental group for the 10-meter running test for football players under 15 years old. Study sample: The researcher chose one of the teams, the amateur club Al-Wefaq Sports Club, Sedrata for football, by the intentional method, which is represented in the category of less than 15 years (18) players. The methodology used in the study: The student followed the experimental method by designing the unit group by selecting a sample consisting of one group -Study tools -Sources and references -Personal interviews -Physical exams. Findings: The open training program using the repetitive training method contributed positively to the development of speed and the skill of running with the ball for football players under 15 years old. The most important suggestions and future prospects: * Organizing roundabouts and scientific forums for trainers to raise their knowledge capabilities and provide them with all that is new in the field of training. * The trainers seek to use technology and modern devices in training. * Basic training is supported and encouraged by providing all material capabilities. * Diversifying similar studies on various sports activities, especially individual ones Studying the effect of repetitive training on physiological indicators. * Using repetitive training more widely in football. ...............................................................ملخص الدراسة................................................................ عنوان الدراسة :اثر برنامج تدريبي مقترح بطريقة التدريب التكراري في تطوير السرعة ومهارة الجري بالكرة لدى لاعبي كرة القدم فئة اقل من 15 سنة الهدف من الدراسة:معرفة اثر التدريب التكراري ضمن برنامج تدريبي مقترح لتطوير السرعة ومهارة الجري بالكرة لدى لاعبي كرة القدم فئة اقل من 15 سنة مشكلة الدراسة: البرنامج التدريبي المقترح باستخدام التدريب التكراري يساهم في تطوير السرعة ومهارة الجري بالكرة لدى لاعبي كرة القدم فئة اقل من 15 سنة فرضيات الدراسة 1/ الفرضية العامة : يؤثر البرنامج التدريبي المقترح باستخدام التدريب التكراري إيجابا في تطوير السرعة و مهارة الجري بالكرة لدى لاعبي كرة القدم أقل من 15 سنة 2/الفرضيات الجزئية :  توجد فروق دالة احصائيا بين القياسين القبلي و البعدي للمجموعة التجريبية لاختبار السرعة 30 متر لدى لاعبين كرة القدم فئة اقل من 15 سنة  توجد فروق دالة احصائيا بين القياسين القبلي و البعدي للمجموعة التجريبية لاختبار الجري 10 متر لدى لاعبين كرة القدم فئة اقل من 15 سنة عينة الدراسة :قام الباحث باختيار فريق واحد من الفرق النادي الهاوي الوفاق الرياضي سدراته لكرة القدم بالطريقة القصدية و المتمثل في فئة اقل من 15 سنة (18)لاعب المنهج المتبع في الدراسة : قد اتبع الطالب المنهج التجريبي بتصميم المجموعة الوحدة و ذلك باختيار عينة تتكون من مجموعة واحدة  أدوات الدراسة  المصادر والمراجع  المقابلات الشخصية  الاختبارات البدنية . النتائج المتوصل إليها : البرنامج التدريبي المفتوح باستخدام طريقة التدريب التكراري ساهم إيجابيا في تطوير السرعة ومهارة الجري بالكرة لدى لاعبي كرة القدم فئة اقل من 15 سنة اهم الاقتراحات و الافاق المستقبلية :  تنظيم دوارات وملتقيات علمية للمدربين لرفع قدراتهم المعرفية وتزويدهم بكل ما هو جديد في مجال التدريب .  سعي المدربين إلى استخدام التكنولوجيا و الاجهزة الحديثة في التدريب  التكوين القاعدي وتدعمه و تشجيعه من خلال توفير جميع الامكانيات المادية  تنويع الدراسات المشابهة على مختلف الانشطة الرياضية وخاصة الفردية  دراسة تأثير التدريب التكراري على المؤشرات الفيزيولوجية  استخدام التدريب التكراري بشكل اوسع في كرة القدم ..............................................résumé............................................................ Titre de l'étude : L'effet d'un programme d'entraînement proposé utilisant la méthode d'entraînement répétitif pour développer la vitesse et l'habileté de courir avec le ballon pour les joueurs de soccer de moins de 15 ans. Le but de l'étude : Connaître l'effet de l'entraînement répétitif dans un programme d'entraînement proposé pour développer la vitesse et l'habileté de courir avec le ballon pour les joueurs de football de moins de 15 ans. Problématique de l'étude : Le programme d'entraînement proposé utilisant l'entraînement répétitif contribue au développement de la vitesse et de l'habileté à courir avec le ballon chez les joueurs de soccer de moins de 15 ans. hypothèses d'étude 1/ L'hypothèse générale : Le programme d'entraînement proposé par entraînement répétitif affecte positivement le développement de la vitesse et de l'habileté à courir avec le ballon chez les footballeurs de moins de 15 ans. 2/ Hypothèses partielles : Il existe des différences statistiquement significatives entre les mesures pré et post du groupe expérimental pour le test de vitesse de 30 mètres pour les joueurs de football de moins de 15 ans. Il existe des différences statistiquement significatives entre les mesures pré et post du groupe expérimental pour le test de course à pied de 10 mètres pour les joueurs de football de moins de 15 ans. Échantillon d'étude : Le chercheur a choisi une des équipes, le club amateur Al-Wefaq Sports Club, Sedrata pour le football, par la méthode intentionnelle, qui est représentée dans la catégorie des joueurs de moins de 15 ans (18 joueurs). La méthodologie utilisée dans l'étude: L'étudiant a suivi la méthode expérimentale en concevant le groupe de base en sélectionnant un échantillon composé d'un groupe -Outils d'étude -Sources et références -Entretiens personnels -Examens physiques. Résultats: Le programme d'entraînement ouvert utilisant la méthode d'entraînement répétitif a contribué positivement au développement de la vitesse et de l'habileté à courir avec le ballon pour les joueurs de football de moins de 15 ans. Les suggestions les plus importantes et les perspectives d'avenir : * Organiser des manèges et des forums scientifiques pour les formateurs afin d'augmenter leurs capacités de connaissance et leur apporter toutes les nouveautés dans le domaine de la formation. * Les formateurs cherchent à utiliser la technologie et les appareils modernes dans la formation * La formation de base est soutenue et encouragée en fournissant toutes les capacités matérielles. * Diversifier les études similaires sur diverses activités sportives, notamment individuelles * Étudier l'effet de l'entraînement répétitif sur les indicateurs physiologiques * Utiliser plus largement l'entraînement répétitif dans le football
دراسة ميدانية لفرق أكاديمية الوفاق الرياضي –سدراتة- سوق اهراس-